Influences Preceding “Nunatsiavut” Self-Determination: Historical, Political and Educational Influences on the People of Northern Labrador (Canada) - Anderson, Kirk David (The Australian Journal of Indigenous Education, 2007)
Abstract What were the influences on the Inuit of Northern Labrador preceding the creation of the self-governing territory of Nunatsiavut? What are the preterritorial influences of the Inuit on the territory’s five schools? To answer these questions and to share the success of one Indigenous people, the Nunatsiavut Inuit (the Inuit of Northern Labrador, Canada), this paper traces their survival, recovery, and development as they reclaim their right to self-determination (Smith, 1999). As part of this process, the paper reports such influences as: the bicultural and assimilationist forces (Moravian missionaries and the governments of Newfoundland), the rise and successful influence of the Labrador Inuit Association as a precursor to the Nunatsiavut Assembly, and the Inuit influence on schools in the region. This paper concludes with a discussion of the nature of northern isolation as a source of economic and cultural strength, which may have enabled the Nunatsiavut Inuit to resist complete assimilation, a factor in Nunatsiavut Inuit survival and increased potential for successful self-determination.